Świadomość metodologiczna studentów oraz studencki projekt badawczy w dydaktyce metodologii badań glottodydaktycznych = Students` awareness of methodology and a students? research project as a methodological tool in applied linguistics - Izdebska-Długosz, Dominika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article outlines the thematic scope and objectives of the lecture on research methodology in language teaching in the postgraduate program Teaching Polish as a foreign and second language at the Faculty of Polish Studies at the Jagiellonian University. The analysis comprises the views expressed by the freshmen and sophomores-to-be indicating their increased methodology awareness. The review of the student research projects in which the students apply the methodological notions they have learnt in the lectures for the first time show their preferences for strategies, methods, and research techniques.
Keywords: glottodydaktyka; metodologia badań; projekt badawczy; studenci; research methodology; linguistics; language learning; research project; students